Lessons from low seroprevalence of SARS‐CoV‐2 antibodies in schoolchildren: A cross‐sectional study. Issue 4 (15th February 2021) - Szépfalusi, Zsolt; Schmidthaler, Klara; Sieber, Justyna; Kopanja, Sonja; Götzinger, Florian; Schoof, Anja; Hoz, Jakub; Willinger, Birgit; Makristathis, Athanasios; Weseslindtner, Lukas; Stiasny, Karin; Bohle, Barbara; et al.
Abstract: Background: Children are discussed as hidden SARS‐CoV‐2 virus reservoir because of predominantly mild or even asymptomatic course of disease. The objective of this cross‐sectional study in May‐July 2020 was to assess the prevalence of SARS‐CoV‐2 antibodies and virus RNA in schoolchildren, consistent with previous infection by contact tracing. Methods: School authorities approached parents for voluntary participation. Interested families were contacted by the study team. A nasal and oropharyngeal swab, a blood sample, and a questionnaire were employed. Primary endpoint was the frequency of SARS‐CoV‐2 real‐time PCR (RT‐PCR) and antibody‐positive children. Antibody positivity was assessed by a highly sensitive first‐line ELISA, and a neutralization assay and two other immunoassays as confirmatory assays. Results: Of 2069 children (median age 13 years, IQR 10‐15), 2 cases (0.1%) tested positive for SARS‐CoV‐2 RNA and 26 cases (1.3%) tested positive for specific antibodies. SARS‐CoV‐2‐specific antibodies exhibited detectable virus‐neutralizing activity in 92% (24 of 26 samples). Seropositivity was associated with a history of mild clinical symptoms in 14 children (53.8%), while 12 children (46.2%) remained asymptomatic. Among 13 seropositive children being tested concomitantly with their siblings, only one pair of siblings was seropositive. Contact tracing revealed adult family members and school teachers as potential index cases. Conclusion: In schoolchildren, the infection rate with SARS‐CoV‐2 is low and associated with a mild or asymptomatic course of disease. Virus spreading seemed to occur more likely in intergenerational contacts than among siblings in the same household. The presence of neutralizing SARS‐CoV‐2 antibodies in children may reflect protective adaptive immunity. Abstract :